2015
DOI: 10.12659/msm.893453
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Polymorphisms in DEFB1 and Susceptibility to Digestive Diseases

Abstract: BackgroundAberrant expression of defensins is implicated in the pathogenesis of digestive diseases. However, the contribution of specific defensins and the influence of their genetic polymorphisms on the progression of digestive diseases remain controversial. In the present meta-analysis, we investigated the association between DEFB1 SNPs and the susceptibility to digestive diseases.Material/MethodsCase-control studies that reported the correlation between DEFB1 SNPs and the susceptibility to digestive disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, further research is needed to obtain conclusive data. In addition, single nucleotide polymorphisms (SNPs) of the hBD-1 gene was connected with the pathogenesis of inflammatory bowel diseases and chronic gastritis [93], as well as oral diseases [94].…”
Section: Role Of Host Defense Peptides In Inflammationmentioning
confidence: 99%
“…However, further research is needed to obtain conclusive data. In addition, single nucleotide polymorphisms (SNPs) of the hBD-1 gene was connected with the pathogenesis of inflammatory bowel diseases and chronic gastritis [93], as well as oral diseases [94].…”
Section: Role Of Host Defense Peptides In Inflammationmentioning
confidence: 99%
“…This base change is thought to lead to a decreased production of defensin β-1 production and higher expression levels. 20, 21 The G allele is also more common in individuals with severe acute pancreatitis and less predominant in individuals with diabetes and S. aureus nasal colonization 8, 20, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…DEFB1 is an important antimicrobial peptide in epithelial tissues and functions as a primary and broad-spectrum response by the host innate defense system [ 88 , 90 , 91 ]. Multiple studies reported that the low expression of DEFB1 , due to genetic polymorphisms, is associated with the pathogenesis of digestive diseases [ 92 , 93 ]. In contrast, other studies showed no such correlation between DEFB1 genetic polymorphisms and digestive diseases [ 94 , 95 ].…”
Section: Hp Virulence Factorsmentioning
confidence: 99%